2012
DOI: 10.1186/1754-6834-5-12
|View full text |Cite
|
Sign up to set email alerts
|

Separate hydrolysis and co-fermentation for improved xylose utilization in integrated ethanol production from wheat meal and wheat straw

Abstract: BackgroundThe commercialization of second-generation bioethanol has not been realized due to several factors, including poor biomass utilization and high production cost. It is generally accepted that the most important parameters in reducing the production cost are the ethanol yield and the ethanol concentration in the fermentation broth. Agricultural residues contain large amounts of hemicellulose, and the utilization of xylose is thus a plausible way to improve the concentration and yield of ethanol during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(25 citation statements)
references
References 37 publications
1
20
0
1
Order By: Relevance
“…Ko et al (2016) reported for the SXA-R2 P-E strain, expressing the XI pathway, in oak hardwood hydrolysate with approximately 6 g/L of acetic acid, an ethanol yield of 0.43 g/g. Studies using wheat straw as feedstock with industrial recombinant yeast strains expressing also the XR-XDH pathway have reported ethanol yields from 0.39 g/g (KE6-12 strain) up to 0.48 g/g, with TMB3400 (Erdei et al, 2012(Erdei et al, , 2013. While these results were obtained in fed-batch fermentation, the ethanol yields obtained in this work stand among those.…”
Section: Xylose Consumption Of Metabolic Engineered Strains On Lignocmentioning
confidence: 52%
“…Ko et al (2016) reported for the SXA-R2 P-E strain, expressing the XI pathway, in oak hardwood hydrolysate with approximately 6 g/L of acetic acid, an ethanol yield of 0.43 g/g. Studies using wheat straw as feedstock with industrial recombinant yeast strains expressing also the XR-XDH pathway have reported ethanol yields from 0.39 g/g (KE6-12 strain) up to 0.48 g/g, with TMB3400 (Erdei et al, 2012(Erdei et al, , 2013. While these results were obtained in fed-batch fermentation, the ethanol yields obtained in this work stand among those.…”
Section: Xylose Consumption Of Metabolic Engineered Strains On Lignocmentioning
confidence: 52%
“…Fed-batch SHCF of steam-pretreated wheat straw has previously been shown to enhance xylose utilization [22,23]. However, regardless of chosen prefermentation configuration a single addition of enzymatic hydrolyzate elicited higher xylose utilization and ethanol yields than corresponding fedbatch cofermentations with two additions (Table 3).…”
Section: Effect Of Number Of Additions Of Enzymatic Hydrolyzatementioning
confidence: 97%
“…Both strategies have advantages, and the choice is strain and feedstock dependent. Modifications to the fundamental strategies have been implemented to improve fermentation performance and substrate utilization [22][23][24]. Fed-batch design has been implemented to promote coconsumption in SHCF [22,23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The microbial strain selected for the fermentation of pentose sugars has a large effect on ethanol yield (Anuj et al 2011). Therefore, naturally xylose-fermenting yeasts such as Candida shehatae and Pichia stipitis have been widely studied because of their ability to ferment xylose into ethanol (Borbala et al 2012). Pichia stipitis is considered a promising strain because it can ferment a wide range of sugars, including cellobiose (Nigam 2001).…”
Section: Introductionmentioning
confidence: 99%